Evaluation of bcl-2, bax and c-erbB-2 Levels in Chronic Otitis Patients with or without Cholesteatoma - Isik, Ozgur; Karlidag, Turgut; Simsek, Bengu Cobanoglu; Keles, Erol; Kaygusuz, Irfan; Yalcin, Sinasi; Sapmaz, Emrah (Galenos Yayincilik, 2015)
Objective: The aim of this study was to evaluate bcl-2, bax, and c-erbB-2 expressions in primary and secondary acquired cholesteatoma and to indicate the role of apoptosis and accompanying increased cellular proliferation in the pathogenesis of cholesteatoma. Methods: Samples obtained from the skin of the external ear canal (EEC) of patients operated for chronic otitis media (COM) without cholesteatoma constituted Group 1; samples from the EEC skin of patients in Group 3 operated for COM with cholesteatoma and from the EEC skin of patients in Group 4 constituted Group 2; samples obtained from the cholesteatoma matrix of patients operated for COM with primary acquired cholesteatoma constituted Group 3; and samples obtained from the cholesteatoma matrix of patients operated for COM with secondary acquired cholesteatoma constituted Group 4. The assessment of the positive cell ratio was based on the presence of the following findings and was semiquantitatively classified into four groups: 0, no staining; + cell staining (weak positive staining: 1%-33%); ++ cell staining (moderately positive staining: 34%-66%); and +++ cell staining (strong positive staining: 67%-100%). Results: Comparison of the staining scores of bcl-2, bax, and c-erbB-2 revealed a statistically insignificant difference in the staining of samples obtained from the EEC skin (p>0.05). Decreased bcl-2 expression and increased bax and c-erbB-2 expressions were determined in primary and secondary acquired cholesteatoma epithelium compared with the EEC skin of patients operated for COM with or without cholesteatoma, and the differences were found to be statistically significant (p<0.05). Conclusion: In acquired cholesteatoma epithelium, the finding of decreased bcl-2 expression as well as increased bax and c-erbB-2 expressions compared with the EEC skin is an indicator of the increase in both cellular proliferation and apoptosis.
Keywords: Cholesteatoma; apoptosis; cell proliferation; bcl-2; bax; c-erbB-2